ISLAMIC RELIGIOUS EDUCATION TEACHERS' STRATEGIES IN IMPROVING STUDENTS' RELIGIOUS CHARACTER AT MAS AL WASHLIYAH PAKAM VILLAGE - Mhd. Prayuda; Hasnil Aida (Jurnal Bilqolam Pendidikan Islam, 2026)
This study aims to analyze the strategies employed by Islamic Religious Education teachers in improving students’ religious character at MAS Al Washliyah. The focus of the study is directed toward the forms of strategies implemented by teachers, the supporting and inhibiting factors, and their impact on the development of students’ religious character within the school environment. This research employed a qualitative approach using a descriptive research design. Data were collected through observations, interviews with Islamic Religious Education teachers and students, as well as documentation of religious activities conducted at the school. The data analysis techniques included data reduction, data presentation, and conclusion drawing. The results of the study indicate that the strategies used by Islamic Religious Education teachers in enhancing students’ religious character were carried out through habituation of worship practices, teacher role modeling, providing advice and motivation, and organizing religious activities such as congregational prayers, Qur’an recitation, and commemoration of Islamic holidays. Teachers also applied personal approaches to students in order to build religious awareness and good morals. Supporting factors in implementing these strategies included support from the school principal, a religious school environment, and cooperation between teachers and parents. Meanwhile, the inhibiting factors were the lack of awareness among some students and the influence of the external environment outside the school. This study concludes that the strategies implemented by Islamic Religious Education teachers play an important role in shaping and improving students’ religious character at school.